Penerima Manfaat Bantuan Non Tunai Kartu Keluarga Sejahtera Menggunakan Metode NAÏVE BAYES dan KNN - Putri, Haidah; Purnamasari, Ade Irma; Dikananda, Arif Rinaldi; Nurdiawan, Odi; Anwar, Saeful (Forum Kerjasama Pendidikan Tinggi, 2021)
The Prosperous Family Card is one of the government's programs in accelerating poverty which functions as a marker for the underprivileged. The implementation of the PSC policy is still not optimal due to factors, namely the lack of socialization and information from village and sub-district officials to the community regarding programs issued by the government. This research to classify the beneficiaries of the Prosperous Family Card, because there are still many other disadvantaged families who have not had the opportunity to receive this assistance program. The method used in this research is the Naive Bayes method and the K-NN method. The results of this study are the classification of beneficiaries from 6,491 KKS recipients with the K-NN Algorithm method yielding an accuracy value of 66.46% with a distribution in 5 villages, including pred Argasunya class precision 64.90% pred Harjamukti class precision 65.18% pred Kalijaga class precision 66.64% pred Kecapi class precision 68.44% pred Prohibition class precision 68.34% while the Naïve Bayes algorithm is classified with true in each kelurahan with true Argasunya distribution of 1,196 KKS class precision 100%, true Harjamukti 1,339 KKS class precision 100%, true Kalijaga 2,067 KKS class precision 100%, true Kecapi 1,137 KKS class precision 100%, true Prohibition 744 KKS(1 KKS true Argasunya, 1 KKS true Harjamukti, 3 KKS true Kalijaga, 3 KKS true Kecapi) class precision 98.64%. the accurasy value of the Naïve Bayes algorithm model is 99.88%.